Formally Encoding Morphomicity - Géraldine Walther (2012)
While morphology can be a means to convey meaning, there are also cases where it stands alone. Since (Aronoff, 1994), the term morphome has become a way to name units of linguistic representation that are “forms without meaning”. The term morphome may also be used to denote cases where non-homogeneous morphosyntactic feature structures realise a specific, fixed, set of sound forms. Introducing Parsli, a formal inferential realisational model in the sense of (Stump, 2001), we propose a way to formally represent the notion of morphomicity, i.e., the fact of exhibiting properties that are best explained using the notion of morphome.